Can Bos indicus cattle breeds be discriminated by differences in the changes of their sweat gland traits across summer and winter seasons? - Nagib Nascimento, Carolina Cardoso [UNESP]; Carvalho Fonseca, Vinicius de Franca [UNESP]; Fuller, Andrea; Melo Costa, Cintia Carol de [UNESP]; Beletti, Marcelo Emilio; Bueno de Mattos Nascimento, Mara Regina (Elsevier B.V., 2019)
This study addresses the hypothesis that Bos indicus cattle breeds can be discriminated by the changes that occur in their sweat gland traits between summer and winter seasons in tropical conditions. Samples of the skin were taken from six Bos indicus cattle breeds (eight subjects per breed), including Nellore, Cangaian, Gyr, Guzerat, Punganur, and Sindhi in winter and summer. The sweat gland epithelium (mu m), glandular portion length (mu m), sweat gland duct length (mu m), gland depth (mu m), and sweat gland density (cm(2)) were determined. Principal component analyses were performed to address the overall structure of breed's group, together with confirmatory analyses by the least squares procedures. Exploratory analysis showed that cattle breeds presented patterns of dissimilarity in the changes in their skin and sweat glands traits between winter and summer seasons. Breeds were separated into three groups under the two principal components, which represented 77.26% of the total variance. The first group was composed of Sindh and Guzerat cattle, which did not present modifications in the parameters assessed between seasons. The most visible alterations were observed in Gyr cattle (third group). In fact, confirmatory analyses showed that glandular portion length, sweat gland duct length, gland depth, and sweat gland density of the Gyr cattle increased (P < 0.05) during the summer season. In conclusion, the results of this investigation demonstrated that morphological traits of the skin and sweat glands associated with seasonal changes in tropical conditions were able to discriminate among Bos indicus cattle breeds.
Keywords: Hot climate; Phenotypic plasticity; Skin traits; Tropical cattle breeds